PENGARUH PENGUNGKAPAN LAPORAN KEBERLANJUTAN TERHADAP KINERJA KEUANGAN PERUSAHAAN - Yuliersi Amartha; Wahyu Meiranto (Diponegoro Journal of Accounting, 2025)
This study aims to provide empirical evidence regarding the effect of sustainability report disclosure on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). The independent variables in this study are sustainability report disclosure measured in aggregate, as well as partial disclosure indices consisting of economic performance disclosure, environmental performance disclosure, and social performance disclosure. Financial performance as the dependent variable is measured using Return on Assets (ROA) and Return on Equity (ROE), with firm size and leverage as control variables.This research employs secondary data consisting of corporate sustainability reports for the period 2021–2023 as the basis for measuring sustainability disclosure, along with financial performance data (ROA and ROE) obtained from the Bloomberg terminal for the period 2022–2024. The sample was selected using purposive sampling, resulting in 74 companies with a total of 181 observations. The study applies a quantitative approach with multiple linear regression analysis. Data processing and analysis were conducted using EViews 13 software.The results indicate that aggregate sustainability disclosure, economic performance disclosure, and environmental performance disclosure do not have a significant effect on financial performance, whether proxied by ROA or ROE. Meanwhile, social performance disclosure has a positive and significant effect on ROA, but does not significantly affect ROE. These findings suggest that the social aspect of sustainability reports provides a faster and more direct impact on financial performance compared to economic and environmental aspects.